The eradication of shanty towns in the City of Buenos Aires: specific features and general context (1976-1983) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
This article explores the eradication of shanty towns that took place in the city of Buenos Aires during the dictatorship that lasted from 1976 to 1983. The eradication assumed an unprecedented scale, considering the number of affected inhabitants, the size of the zones cleared out in a compulsory way, and the violence implemented in eviction operations. Throughout this period, a series of deep structural transformations occurred, associated with the end of import substitution industrialization and the beginning of a strong market liberalization that, within a framework of illegal repression, dramatically aggravated the precarious living and working conditions suffered by the shanty town dwellers. Under these circumstances, the eradication tended to guarantee an increase in the market value of real state through the expulsion of around 200.000 people from the city.
Keywords: Shanty towns; Dictatorship; History; Eradication.